2014
DOI: 10.1021/ol501704q
|View full text |Cite
|
Sign up to set email alerts
|

Pd(0)-Catalyzed Alkenylation and Allylic Dearomatization Reactions between Nucleophile-Bearing Indoles and Propargyl Carbonate

Abstract: Spiroindolenine derivatives were synthesized by intermolecular Pd-catalyzed dearomatization of indoles. The reaction between nucleophile bearing indoles and propargyl carbonate proceeds in a cascade fashion providing spiroindolenines or spiroindolines in good to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…In 2014, the Rawal group and we independently reported an intermolecular cascade dearomatization reaction of indole‐based bisnucleophiles with propargyl carbonate, leading to a series of spiroindolenines and spiroindolines. Moderate enantioselectivity (≤77 % ee ) was achieved for limited substrates (Scheme , reaction 1) . Rawal and co‐workers found that the indole N−H moiety could participate in the cyclization process when the nucleophilic side chain was decorated at the C2 position of the C3 methyl substituted indole (Scheme , reaction 2) .…”
Section: Figurementioning
confidence: 99%
“…In 2014, the Rawal group and we independently reported an intermolecular cascade dearomatization reaction of indole‐based bisnucleophiles with propargyl carbonate, leading to a series of spiroindolenines and spiroindolines. Moderate enantioselectivity (≤77 % ee ) was achieved for limited substrates (Scheme , reaction 1) . Rawal and co‐workers found that the indole N−H moiety could participate in the cyclization process when the nucleophilic side chain was decorated at the C2 position of the C3 methyl substituted indole (Scheme , reaction 2) .…”
Section: Figurementioning
confidence: 99%
“…A similar strategy, which was developed around the same time by the You and Rawal groups, is the use of propargyl carbonates in intermolecular reactions; these reactions are proposed to proceed first by the interception of a typical η 3 ‐π‐allenylpalladium species by a nucleophile tethered onto the indole, before undergoing a protonation–spirocyclisation sequence to form the spirocyclic indolenine products (Scheme ). The contribution by You and co‐workers concerns the reaction of malonates 182 with methyl propargyl carbonate, [Pd 2 (dba) 3 ] and an appropriate phosphine ligand, to afford spirocyclic indolenines 183 in moderate to excellent yield, with preliminary results suggesting that an asymmetric variant is possible using ( R )‐segphos or related derivatives . Meanwhile, Rawal and co‐workers reported the reaction of a variety of indole‐tethered pro‐nucleophiles, [Pd 2 (dba) 3 ], xantphos, and in some cases a base, to furnish an impressive variety of spirocyclic indolenines 185 / 186 , generally in good yield .…”
Section: Indole Dearomatisationsmentioning
confidence: 99%
“…The contribution by Youa nd co-workersc oncerns the reaction of malonates 182 with methyl propargyl carbonate, [Pd 2 (dba) 3 ]a nd an appropriate phosphine ligand,t oa fford spirocyclic indolenines 183 in moderate to excellent yield, with preliminaryr esults suggesting that an asymmetricv ariant is possible using (R)-segphos or relatedd erivatives. [106] Meanwhile, Rawal and co-workersr eported the reaction of av ariety of indole-tethered pro-nucleophiles, [Pd 2 (dba) 3 ], xantphos, and in some cases ab ase, to furnisha ni mpressive variety of spirocyclic indolenines 185/186,g enerally in good yield. [107] Recently,R awal and co-workersa lso described an asymmetric adaptation of this reaction, where in as imilar fashion to You and co-workers, chiral phosphine ligands( 188)w ere used to furnish the indolenines 189 in good to excellent yield and with high enantioselectivity.…”
Section: Additiont Op-allyl Intermediatesmentioning
confidence: 99%
See 1 more Smart Citation
“…In an analogous process, You et al found that the nitrogen nucleophile can be replaced by a malonate in 126 (Scheme 28), 40 thus giving rise to the installation of new all-carbon quaternary centers in spiroindolenines 127 with the same regioselectivity. A range of ester side-chains and indole substituents were successfully examined (127a-c).…”
Section: Scheme 27 Dearomatization Of Tryptamine Derivativesmentioning
confidence: 99%